Analisis Implementasi Sistem Informasi Akuntansi Berbasis E-Commerce Pada Bisnis Online “Belanja Diaku” Di Era Digital 5.0 - Rahmadhany, Arwinda (Institut Agama Islam Negeri (IAIN) Madura, 2025)
The development of digital technology in the Industry 5.0 era has significantly transformed business operations, particularly in the implementation of e-commerce-based Accounting Information Systems (AIS). This study aims to analyze the implementation of AIS within the online thrift fashion business, Belanja Diaku, which utilizes Shopee and TikTok Live as its primary sales and marketing platforms. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation. The findings reveal that the AIS implementation at Belanja Diaku is effective in recording sales and purchase transactions, with integration across e-commerce platforms and digital payment methods such as ShopeePay and virtual accounts. Additionally, TikTok Live streaming serves as an effective marketing tool that enhances customer engagement. However, challenges remain, including manual inventory control and limited automation in financial reporting and analysis. This study contributes to understanding how digital technologies and AIS integration can support MSMEs’ operational efficiency in the Industry 5.0 era.